Migration, Remittances, and the Brain Drain - de Melo, Jaime (World Bank, 2012)
International migration will be one of the major challenges of the twenty-first century. Lower transaction and communication costs have already greatly eased the formation of migrant networks and reduced migration costs, for long a deterrent to migration from developing countries to developed countries. Migratory pressures will also increase as falling dependency ratios in developing countries contribute to the swelling of their labor forces. Remittances from migrants to developed countries should then help to close the developing-country developed-country divide.